Regulation of the Hippo–YAP pathway by protease-activated receptors (PARs) - Mo, Jung-Soon (Cold Spring Harbor Laboratory Press, 2012)
The Hippo signaling pathway plays a crucial role in tissue growth and tumorigenesis. Core components of the Hippo pathway include the MST1/2 and Lats1/2 kinases. Acting downstream from the Hippo pathway are the YAP/TAZ transcription coactivators, which are inhibited through phosphorylation by Lats. However, upstream signals that regulate the Hippo pathway have not been well delineated. Here we report that stimulation of protease-activated receptors (PARs) activates YAP/TAZ by decreasing phosphorylation and increasing nuclear localization. PAR1 acts through G(12/13) and Rho GTPase to inhibit the Lats1/2 kinase. Our observations establish thrombin as a physiological signal for the Hippo pathway and implicate Hippo–YAP as a key downstream signaling branch of PAR activation.